Aesthetics, ethics and fashionable veiling: a debate in contemporary Turkey. Issue 2 (3rd July 2017) - Crăciun, Magdalena
Abstract : Observant Muslim women all over the world experiment with materials and styles, find inspiration in past and present, Eastern and Western fashions, and create new types of covered dress. This fashionable veiling has also become the topic of heated debates. This article builds on an ethnographic study that highlights the debate over fashionable veiling within Turkey. According to the conceptualisation of the revivalist movement, veiling is an ethical practice of self-cultivation. The dress hypostatises a particular religiously sanctioned aesthetics (an aesthetics of the proper form); and the practitioner commits herself to a religiously defined conduct (an aesthetics of the correct posture). Fashionable veiling is (also) a sartorial practice of self-enhancement. It demonstrates experimentation within a religiously sanctioned aesthetics; and the practitioner's public behaviour evidences both conformity with and transgression of religiously defined conduct. The article approaches fashion as a realm of the aesthetic and finds guidance in anthropological discussions of 'Islamic art', 'ordinary ethics' and 'everyday Islam'. I argue that the debate over fashionable veiling among religious conservatives provides insight into what kind of relationship there can be between ethics and aesthetics, and who is qualified to define it. Religious conservatives emphasise that in veiling the only possible and permissible relationship between ethics and aesthetics is one of subordination of aesthetics to ethics. In contrast, headscarf-wearing fashion professionals, the most visible practitioners of this type of veiling, claim that in fashionable veiling the relationship between ethics and aesthetics is one of identity, namely, aesthetics as ethics.